Tensile and flexural strength of flax fiber reinforced composites with and without chemical treatment - Paulo, A.B.I. (2022)
PLA composites were reinforced with a natural fiber, flax fiber. A Taguchi L18 matrix was created and for each test 6 specimens were run, varying the temperature, fiber percentage, fill percentage of the specimens, and whether or not the flax fiber was treated. As for the treatment of flax, when applicable, it was treated with sodium hydroxide (NaOH). The temperatures used are 190°C, 200°C and 220°C. The percentage of fiber varies in 10, 15 and 20 fiber strands. The filling percentage of the specimen varies between 25%, 50% and 100%. This was followed by a study of the tensile and flexural strength of the reinforced composites. The optimal combinations for increased tensile and flexural strength were obtained with the following parameters for tensile: with/without chemical treatment, with a temperature of 200°C, 10 fibers and a filler percentage of 100%. For bending the parameters are: with chemical treatment, a temperature of 190°C, 10 fibers and a fill percentage of 100%. With the confirmation tests a value for the maximum tensile stress of 19.38 MPa and for bending of 73.20 MPa was obtained.